DIKSI, RIMA, TEMA, DAN AMANAT PUISI ANAK-ANAK DALAM BALON KEINGINAN (ANTOLOGI CERPEN DAN PUISI ANAK-ANAK) KARYA KORRIE LAYUN RAMPAN - Suwardo, Fx; Fitriayu, Bernadet (Educatio Vitae, 2017)
This research goals is to find out and explain the rhyme, diction, theme, poetry and speeches of children contained in Kids Poetry Balon Keinginan (The Anthology of Short Stories and Poetry of Children) written by Korrie Layun Rampan. This research uses qualitative descriptive method. This means that the research is based on descriptive data in the form of words, phrases, sentences, contained in the array, the temple, and a unit of poetry on poetry of children contained in Kids Poetry Balon Keinginan (The Anthology of Short Stories and Poetry of Children) written by Korrie Layun Rampan, which could supporting the aspects examined and researchers as a research instrument. From the analysis of the obtained results are as follows (1) Diction used there are two, namely diction in denotative there are 9 of 9 poetry diction and konotatif there are 10 out of 10 poetry, (2) Rhyme can be distinguished on the basis of (a) rhyme based on sound there are 5, (i) 25 perfect rhyme,  (ii) 30 unperfect rhyme, (iii) 12 rhyme alliteration, (iv) 2 rhyme dissonance, (v) 13 rhyme absolute, (b) there are 5 in-line layout (i) 38 initial rhyme, (ii) 29 rhyme middle, (iii) 25 rhyme end, (iv) 4 rhyme upright, (c) there are 5  temple layout based on rhyme, (i) 2 crossed rhyme, (ii) 2 hug rhyme, (iii) 6 rhyme continue, (iv) 1 rhyme paired, (v) 8 broken rhyme. (2) 6 kinds of themes. (3) Mandate or message poet delivered to readers, namely: (a) we should always give thanks to God, (b) care to fellow who experienced hardship, (c) respect to warrior of our nation, (d) preserve the environment that exists around us, (e) love people that are all around us, and (f) learn seriously.